Implementasi Data Mining Pada Sistem Informasi Menggunakan Fp-Growth - Dayu Renita; Eka Dyar Wahyuni; Seftin Fitri Ana Wati (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
The use of technology in various fields in the current era is very helpful to be more efficient. One of them is in utilizing information systems to process data. This research aims to analyze transaction data that is useful for small and medium business managers. The data collection methods used in this research are interviews and observations. Website development using Visual Studio with Python programming language and MySQL database. The information system designed consists of several pages including dashboard, master data, data exploration and fp-growth analysis page. The results of this study are in the form of an Information System for analyzing the fp-growth algorithm using the flask library to facilitate users in obtaining information on the results of the analysis. The pages contained in the system are the login page, dashboard page, master data page, data exploration page and fp-growth page which contains analysis results.